The Role of Neutron Absorbers in Soliton Wave Creation Using Heavy Water as a Diffusive Medium - Shakeri, A.; Abbasi, K.; Hosseinimotlagh, S. N.; Zarei, M. A.; Rezaei, V. R.; Bayat, J.; Pour, A. G.; Vanaie, H. R.; Rasati, E. (Atom Indonesia, 2026)
One of the simplest nuclear fission reactor designs is the soliton reactor. In these reactors, neutrons reduce the toxicity of fissile materials in a manner that allows new vital areas appear successively. Therefore, the spatial dependence of the neutron flux, specific power density, and associated particle density exhibit wave phenomena of solitons and emerge from the solution of nonlinear partial differential equations, preserving their shape during propagation. The velocity of the burnup Soliton Wave (SW) is related to the density of the initial Nuclear Fuel (NF) in each Neutron Absorber (NA) in the medium. These nonlinear waves can be described by equations describing the atomic flux and density in terms of time and space in the medium. The soliton wave can also be observed in advanced nuclear power systems. Burnup SWs in a propagation medium can be analyzed using the spatial coordinates and position of the NA in a propagation region. The aim of this work is to investigate the burnup SW characteristics by selecting various isotopic neutron absorbers in the slab reactor core. Our computational findings show that the SW burning rate is affected by increasing the diffusion coefficient. However, both the diffusion length and the Length of Transient (LOT) increase with increasing the diffusion coefficient. Interestingly, the ratio of LOT to diffusion length remains constant. Furthermore, while increasing the diffusion coefficient leads to a higher Transient of Time (TOT), the ratio between TOT and characteristic time remains constant.